Bladeless dust collection system to prevent scattering in cosmetics manufacturing process - Nana TSURUTA; Michihiro HAKODA; Ken’ichi YANO; Yohei NAGAMITSU; Yoshiyuki HIRAYAMA (Nihon Kikai Gakkai ronbunshu)
During the powder feeding process in the manufacture of cosmetics, powder is dispersed into the air as dust. If inhaled by workers, the dust can have adverse effects on health, such as dust lung and asthma, and can also lead to contamination of the work environment and of the product. Therefore, dust control measures are essential in the powder feeding process. However, production efficiency is declining due to longer feeding times, and new dust control measures are necessary to ensure worker safety and improve production efficiency. The purpose of this paper is to develop a new dust collection system that can prevent dust generation and improve production efficiency in the manufacturing processes of cosmetics. Specifically, we propose a bladeless dust collection system designed to prevent powder dispersion and enhance the adsorption of powder particles onto the liquid surface. This is achieved by elucidating the forces exerted on the powder particles by the airflow. The effectiveness of the proposed system is demonstrated through powder feeding experiments. The powder feeding was carried out under conditions identical to those in the actual cosmetics manufacturing process. It was observed that dust control was achievable, confirming the absence of any practical issues. Furthermore, because the dust collection system can be installed in accordance with the agitation location, it is possible to implement dust control measures anywhere, and this mobility should improve production efficiency. In conclusion, the effectiveness of the bladeless dust collection system was confirmed.